A reevaluation of specimens of Mesocoelium monas (Platyhelminthes: Digenea: Mesocoeliidae) from the Natural History Museum, UK and the United States National Parasite Collection, USA - Calhoun, Dana M.; Dronen, Norman O. (Zootaxa, 2012)
A total of 67 specimens from the National History Museum, London, UK and from the United States National ParasiteCollection, Beltsville, USA, which had previously been identified as Mesocoelium monas Rudolphi, 1819 from a varietyof definitive hosts (amphibians, reptiles and a fish), were reevaluated using available literature and the keys to nine bodytypes of species developed by Dronen et al. (2012). Fifteen specimens were of insufficient quality to be placed into a bodytype. In the remaining 52, only four body types (mesembrinum, monas, lanceatum, and pesteri) were encountered. Noneof the 52 specimens conformed to either the original description of M. monas by Rudolphi in 1819 or the subsequent re-description by Freitas in 1958. Although some authors have proposed sweeping synonymies of species in the genus re-ducing the number of species to as few as four in a study by Nasir & Dìaz in 1971, the results of the present study suggestthat there are likely numerous species worldwide. The usefulness of some characters in separating species of Mesocoelium is discussed.